Ultrathin carbon layer stabilized metal catalysts towards oxygen reduction1. Issue 26 (14th July 2015) - Cheng, Kun; Kou, Zongkui; Zhang, Jian; Jiang, Min; Wu, Hui; Hu, Lin; Yang, Xiaoyu; Pan, Mu; Mu, Shichun
<x xml:space="preserve">Abstract</x> Synthetic strategy and anchoring effect of ultrathin carbon layer (UTCL) coated Pt nanoparticles on carbon supports.